IRE1 Less Common Homozygous Genotype in Families With Positive History of Cancer and Individuals Born With Cleft Lip/Palate. Issue 5 (July 2021) - Assis, Ionária O.; Lacerda, Rosa Helena W.; Cavalcante, Bianca G.N.; Bezamat, Mariana; Modesto, Adriana; Vieira, Alexandre R.
Abstract : Abstract: The aim of this study was to test if the marker rs196929 in IRE1 associated with cleft lip and palate depending on the family history for cancer. A consecutive sample of 836 individuals were recruited between April and October of 2019 (303 born with cleft lip and palate, 256 relatives mostly of the maternal side of individuals born with cleft lip and palate, and 277 unaffected unrelated individuals). Parents or guardians of the children answered a questionnaire with basic demographic information about their children and their family history of cleft lip and palate and cancer. DNA was obtained from whole saliva and IRE1 rs196929 was genotyped using TaqMan chemistry and end-point analysis. Over-representation of alleles was determined using chi-square as implemented in PLINK using an alpha of 0.05. There was an excess of less common homozygotes of IRE1 rs196929 among relatives of individuals born with cleft lip and palate when they had positive family history of cancer in comparison with individuals born with cleft lip and palate or with unrelated unaffected individuals ( P  = 0.0006 and P  < 0.001, respectively). This pattern was similar when families reported one type of cancer or multiple ones, or when cancer affecting females (breast or reproductive tract) or the structures of the gastro-intestinal tract were considered. These results provide support for a role of the ER stress IRE1-XPB1 pathway in the higher frequency of cancer in families of individuals born with cleft lip and palate. Abstract : Supplemental Digital Content is available in the text